Literature Review on A Machine Learning Model to Predict Crop, Fertilizers and Diseases - Dr. Suman Kumar Swarnkar, Abhay Kumar Gupta, Ashish Kumar Sahu, Indrajeet Sinha (Mathematical Statistician and Engineering Applications, 2022)
Machine Learningis a part of Computer Science that follows various learning methodology and performs many changes within the set of performance and its task to create it higher than the sooner learning. Agriculture domain is leading supply of states growth. New farmers area unit doesn’t awake to systematic farming technique and their methodology to induce good yielding of crops and if they are available recognize the technique, they’re unable to use at their regional condition. taking correct answer or information this specific drawback information exploitation machine learning may be a exhausting and sophisticated task. the assorted system mentioned below is extremely useful to user to induce agricultural connected queries with its economical answer in straightforward method, prediction of crop in keeping with their regional conditions, identification of diseases and therefore the fertilizers needed to treat these diseases.